2005
DOI: 10.1017/s1464793105006846
|View full text |Cite
|
Sign up to set email alerts
|

Using experimental manipulation to assess the roles of leaf litter in the functioning of forest ecosystems

Abstract: The widespread use of forest litter as animal bedding in central Europe for many centuries gave rise to the first litter manipulation studies, and their results demonstrated that litter and its decomposition are a vital part of ecosystem function. Litter plays two major roles in forest ecosystems: firstly, litterfall is an inherent part of nutrient and carbon cycling, and secondly, litter forms a protective layer on the soil surface that also regulates microclimatic conditions. By reviewing 152 years of litter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
507
5
37

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 643 publications
(575 citation statements)
references
References 137 publications
(317 reference statements)
26
507
5
37
Order By: Relevance
“…The removal of litter affects fungal growth and diversity (Eaton et al 2004; Sayer 2005). Species richness of macrofungi therefore increased with increasing litter cover (Figure 3(b)).…”
Section: Discussionmentioning
confidence: 99%
“…The removal of litter affects fungal growth and diversity (Eaton et al 2004; Sayer 2005). Species richness of macrofungi therefore increased with increasing litter cover (Figure 3(b)).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the greatest differences in soil water content between trenched and untrenched soil during the dry season (84% higher in trenched subplots) were observed in the LĂŸ plots where the thick litter cover protected the soil from evaporation and drying (Marthews et al, 2008), and the smallest difference (32% higher in trenched subplots) was observed in the LÀ plots (Fig. 3), where the lack of litter probably lead to greater evaporation from the soil surface (Walsh and Voight, 1977;Sayer, 2006).…”
Section: Rooterhizosphere Respirationmentioning
confidence: 97%
“…For example, litter exclusion can result in soil drying caused by greater evaporation from the unprotected soil surface and differences in soil water balance (Walsh and Voight, 1977;Sayer, 2006). Reviews and meta-analyses of respiration partitioning studies highlight the difficulties involved in the different methods employed and generally agree that isotopic labelling is the most accurate method with the fewest methodological artefacts (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The differences in soil CO 2 emissions among treatments during winter and summer periods are likely due to altered insulation and soil moisture conditions, which influence soil microclimate and biological processes both directly and indirectly (Sayer, 2006;Veres et al, 2013). Numerous studies have documented the dominant role of temperature in controlling decomposition and soil CO 2 emissions (Chen et al, 2000;Knorr et al, 2005;KotroczĂł et al, 2008;Bond-Lamberty and Thomson, 2010;Smith and Fang, 2010).…”
Section: Soil Temperature and Moisturementioning
confidence: 99%